On whiteness: A conversation between Julian Walker and Rob Lewis - Lewis, Robert; Walker, Julian (Museum and Society, 2026)
Julian, a white woman, is an anti-racism writer and facilitator (who, with Cheryl Garvey designed and delivered the Museums Association programme); Rob Lewis is Director of Transformation at Birmingham Museums Trust, a white man and participant on the Museum Associations pilot Anti-Racist Leadership programme in 2024. This conversation offers a personal reflection on coming to understand whiteness for Rob and Julian and took place following the conclusion of the Anti-Racism programme, and from within the construct of whiteness.